Prática pedagógica em uma escola ribeirinha do município de Laranjal do Jari, estado do Amapá - FERREIRA, Maria de Belém Brandão Andrade (2023)
This research has as its object the pedagogical practice in the riverside context, in the municipality of Laranjal do Jari, state of Amapá. It integrates the investigations of the Research Center in Rural Education, Social Movements and Pedagogical Practices (Nupecamp) and the Research Line Pedagogical Practices: Articulating Elements, of the Graduate Program in Education, Tuiuti University of Paraná. The research starts from the following problem: How are the knowledge and knowledge of the local cultural identity worked in the pedagogical practice of riverside teachers? The general objective is to analyze the relationship between pedagogical practice at school and life in the Cajari River Extractive Reserve, in the Community of Martins, southern region of the State of Amapá. The specific objectives are: to characterize the relationship between the pedagogical practice and the school community, as well as the way the extractivists and riverside dwellers live, their own culture, their family relationships, their beliefs and work; to highlight aspects of life and work in the Martins community and the possibilities for pedagogical practice in the school; to identify marks of life and work in the school notebooks and other productions of the students of the initial years of the Elementary School. The research is based on the historical-dialectical materialist method through bibliographic study and fieldwork in the riverside territory of Laranjal do Jari, with interviews and documentary analysis. The research reveals the need for an adequate education to the martinels, contextualized in the principles of Rural Education. It is concluded that the pedagogical practice in the investigated school is distant from the local culture. The subjects of the field, in their territories, have their specificities and need to have visibility and respect for culture and work in the school context.